FEATURES OF MORPHOLOGICAL CHANGES IN THE INTRAMURAL PART OF THE URETER UNDER THE INFLUENCE OF EXPERIMENTAL HYPOTHYROIDISM (Innovate Conferences, 2025)
It is known that hypothyroidism affects the functional state of all organs and tissues of the body. It has been noted in the literature that in children with hypothyroidism, clinical symptoms such as lagging in the development of psychomotor systems, low mobility, and significant weight gain are observed. Based on the results of experimental studies, the available literature presents data on the study of the morphogenesis of the urinary tract on a hypothyroidism model, functional morphometry of the urinary system, histological reconstruction of the intramural part of the urinary tract and the dynamics of morphological changes in their structures, as well as a comparative analysis of the condition in hypothyroidism with the condition obtained as a result of morphological correction.